Organic, inorganic, and hybrid solar cells : principles and practice - Lin, Ching-Fuh (Wiley, 2012)
"Many books discuss inorganic semiconductor solar cells and some books for organic solar cells, but very few books deal with the composite solar cells that use both organic materials and inorganic semiconductors. The authors view organic and inorganic composite thin-film solar cells as the most promising photovoltaic technology for future energy solutions. Focusing on all aspects of realizing low-cost and long life solar cells, the text covers inorganic, organic, and hybrid materials. This unique guide provides an unparalleled description of the functioning principles and fabrication techniques of organic-inorganic composite solar cells"--